Study on Flame Retardancy and Mechanism of Talc Composite Foams - Li, Xiujuan; Guo, Ruisong; Qian, Xiaodong (Frontiers in Materials, 2021)
Under high temperature, water film forming foam extinguishing agent has poor flame retardancy and low fire efficiency. In order to solve this problem, talc was introduced into foam to form composite foam. The fire resistance and fire extinguishing properties of the composite foam were studied. The results showed that talc composite foam has good flame retardant resistance. when the concentration of talc reaches 40 g/100mL, the 50% liquid separation time of the composite foam was 21.1 min. The fuel burning in the anti burning tank did not ignite the gasoline in the oil pan, and burned out at 51.5 min. It was related to the structure of composite foam and the properties of talc. Due to the introduction of talc, the viscosity of the composite foam increased. The network structure of composite foam was important to the improved foam stability. Talc powder can cover the oil surface to form a dense layer, which can effectively isolating the oil from the air.